Unlocking the Power of Waste Cooking Oils for Sustainable Energy Production and Circular Economy: A Review - Okpo, Samson Onoriode; Edafiadhe, Emozino Donatus (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
In the pursuit for sustainable energy solutions, biodiesel has come to prominence as an alternative to petroleum-derived diesel. This review delves into cutting-edge developments in production of biodiesel, emphasizing use of waste cooking oils (WCOs) as an environmentally friendly raw material. Incorporating waste cooking oils (WCOs) into the biodiesel production process not only tackles environmental issues associated with improper disposal but also adheres to the principles of a circular economy. This manuscript covers various methods and technologies for converting WCOs into high-quality biodiesel, emphasizing economic viability and environmental benefits. It discusses the potential of WCO-derived biodiesel to meet stringent fuel standards and reduce greenhouse gas emissions. Significant progress has been made in using waste cooking oils to generate sustainable energy, aligning with broader initiatives focused on renewable energy and circular economy principles. In summary, the utilization of waste cooking oils for biodiesel production presents an opportunity to shift away from reliance on fossil fuels, thereby fostering circular economy practices and sustainability goals.